Analisis Perhitungan Harga Pokok Produksi pada Usaha Peternakan Ayam Broiler (Studi Kasus pada Umar Farm di Kabupaten Maros) - Amaliah, Wafiq Azizah Reski; Idrus, Mukhammad; Sangkala, Masnawaty (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to analyze the calculation of the cost of production and compare the calculations carried out by the company (Umar Farm) with the full costing method. The variable of this study is singular, namely the calculation of the cost of production using the full costing method. The data used is production cost data for the July-September 2023 period. Data collection techniques use documentation and interviews. The data were analyzed by qualitative descriptive analysis. The results of the study show that there is a difference in the cost of production between the company's method and the full costing method, which is Rp 1,920 per chicken and the difference per kg of chicken is Rp 984. This study concludes that the calculations carried out by the company have not classified the costs correctly so that the calculations produced are smaller